THE IMPACT OF BURNOUT AT WORK ON EMPLOYEE PRODUCTIVITY IN THE REPUBLIC OF SERBIA - Obućinski, Dejan; Davidovac, Zoran; Marković, Zlatomir (ACADEMIC REVIEW, 2025)
This paper examines the impact of burnout on employee productivity in the Republic of Serbia. Burnout represents emotional, physical, and mental exhaustion that occurs as a result of prolonged exposure to workplace stress. Individuals experiencing burnout often feel overwhelmed, hopeless, and distanced from their work. Symptoms may include reduced work performance, fatigue, exhaustion, loss of motivation, as well as physical symptoms such as headaches or digestive problems. The research was conducted on a sample of 1,200 employees in companies across four leading sectors in the Republic of Serbia: the food industry, hospitality, machine industry, and the IT sector. The results indicate that high levels of physical exhaustion arise from excessive workloads, inadequate working conditions, and a lack of recovery time, leading to decreased efficiency and productivity. This research emphasizes the urgent need for interventions that could help reduce physical exhaustion among employees, thereby improving their performance and the quality of services they provide to the community. The findings demonstrate that burnout negatively affects employee productivity in the Republic of Serbia.